Fiqh contribution to sustainable development as a form of islamic law reform in the modernization era - Agustiar; Zaid Barzenji; Ali Saif; Bassam Badar Ja'far Al Kutsairi; Ibrahim bin Salem; Umar Ahmad Salem (Yayasan Azhar Amanaa Yogyakarta, 2024)
Sustainable development is a global challenge that requires a holistic approach, including economic, social and environmental dimensions. Countries with a majority Muslim population have the potential to utilize fiqh, as a system of Islamic law and ethics, to support sustainable development. This research aims to explore the contribution of fiqh To Sustainable Development As a Form Of Islamic Law Reform In The Modernization Era. Using a qualitative approach and descriptive-analytical design, this research examines relevant literature, analyzing policy documents. The research results show that fiqh provides a strong ethical and normative foundation to support sustainable development. Fiqh principles such as justice ('adl), public benefit (maslahat), and amanah (trust) are very relevant in overcoming the challenges of sustainable development. Analysis of policy documents reveals that although there are initiatives to integrate fiqh principles in public policy, implementation is still limited and sporadic. In conclusion, fiqh has great potential to contribute to sustainable development by offering strong ethical and normative guidance for creating a more just and sustainable society. It is recommended that future research conduct in-depth case studies in countries with a majority Muslim population to evaluate the implementation of fiqh principles in sustainable development policies, as well as analyze their effectiveness on sustainable development indicators. In addition, it is important to develop a practical framework for the implementation of fiqh principles, conduct comparative studies with other countries, examine the role of stakeholders, and assess the impact of educational programs and public awareness. Long-term evaluation is also needed to measure the real impact on sustainable development and community welfare.